Services and Supports for Individuals with Autism Spectrum Disorders in the Kingdom of Saudi Arabia - Ahmed, Siddiq; Chitiyo, Morgan; Al-Jaffal, Mohamad (Journal of the American Academy of Special Education Professionals, 2019)
This paper reviews the services and supports that are available to individuals with Autism Spectrum Disorder (ASD) in the Kingdom of Saudi Arabia (KSA). The review focuses on the diagnostic process, early intervention and educational services, family collaboration/parental involvement, instructional practices, and research-based practices. Based on this review, there is need for more research in this area in order to increase awareness regarding ASD and promote better services and rehabilitation programs for people with ASD in the KSA. In addition, it is recommended that general education teachers should take special education courses in their preparation programs so that they can effectively support students with ASD in the inclusive education environment.